A lacrimal drainage pathway disease-associated keratopathy (LDAK) case with non-infectious endophthalmitis - Sho Ishikawa; Takafumi Maruyama; Kei Shinoda (American Journal of Ophthalmology Case Reports)
Purpose: To report a case of lacrimal drainage pathway disease-associated keratopathy (LDAK) with endophthalmitis. Observations: An 80-year-old man with diabetic retinopathy and nephropathy was referred to our hospital with endophthalmitis of the left eye. Slit-lamp examination revealed slight eye discharge, peripheral corneal ulcers, diffuse hyperemia of the conjunctiva, iris synechia, and a large amount of fibrin in the anterior chamber of the left eye. No puncta of the left eye were observed. The patient had undergone trabeculectomy for primary open-angle glaucoma 5 years previously. B-mode echo examination confirmed vitreous opacity in the left eye. We suspected endophthalmitis and performed a par-plana vitrectomy, bacterial culture, and polymerase chain reaction examination for eye discharge, aqueous humor, and vitreous humor. However, no bacteria or viruses were detected. The eye discharge and corneal peripheral ulcers did not improve following surgery. A lacrimal syringe test was performed two weeks after surgery, and bacterial concretion and discharge were observed. We detected Actinomyces in the bacterial concretions and performed dacryocystorhinostomy. After surgery, the corneal ulcer improved, and eye discharge disappeared. Conclusions and importance: LDAK causes corneal perforation and endophthalmitis. In cases of intraocular inflammation with corneal ulcers, a lacrimal syringing test should be performed, even in the absence of lacrimal findings on slit-lamp examination.